Factors Associated with the Resilience of Breast Cancer Patients undergoing Chemotherapy - Ariyani Wisudawati Nira; Mira Triharini; Aria Aulia Nastiti (Pediomaternal Nursing Journal, 2020)
Introduction: The management of chemotherapy in breast cancer requires a long time and cause miscellaneous of side effects. High resilience is needed by breast cancer patients to undergo chemotherapy regularly. This study aimed to analyze factors associated with the resilience of breast cancer patients undergoing chemotherapy.Methods: This study design was cross-sectional. From the total population of 122 breast cancer patients, a sample of 100 participants was selected using a purposive sampling technique. The independent variables were hardiness, education level, economic status, side effects of chemotherapy, family support, and anxiety. The dependent variable was resilience. The instruments of this study were Hardiness questionnaire, Chemothraphy-Symptom Assessment Scale (C-SAS), Family Support questionnaire, Zung-Self Rating Anxiety Scale (ZSRAS), and Connor-Davidson Resilience Scale (CD-RISC). The Spearmen’s Rho was used for statistical analysis.Results: Hardiness (p=0.000; r=0.310), Education Level (p=0.000; r=0.416), Economic Status (p=0.000; r=0.369), Side Effects of Chemotherapy (p=0.004; r=-0.283) and Family Support (p=0.000; r=0.579) have relation with the resilience. Anxiety has no relation with the resilience (p=0.23; r=0.121).Conclusion: The side effects management of chemotherapy and family support were necessary to increase the resilience of breast cancer patients undergoing chemotherapy. It is highly recommended to the next researchers to do some studies about factors associated with the side effects of chemotherapy and nursing intervention, which can reduce the side effects of chemotherapy itself.